Thallium(III) p-tosylate mediated oxidative 2,3-aryl rearrangement: a new useful route to ipriflavone and its analogs - Muthukrishnan, Murugan; Singh, Om V. (Synthetic Communications, 2008)
A new route for the synthesis of ipriflavone, an antiosteoporotic agent, is described that has four steps and 60% yields starting from resacetophenone (2). The key step of the present methodology is thallium(III) p-tosylate mediated oxidative 2,3-aryl rearrangement of flavanone to generate the isoflavone ring system of ipriflavone in a highly efficient manner.
Keywords: Flavanones; ipriflavone; isoflavones; oxidative rearrangement; thallium(III) p-tosylate